Large-scale prediction of stream water quality using an interpretable deep learning approach. (1st April 2023) - Zheng, Hang; Liu, Yueyi; Wan, Wenhua; Zhao, Jianshi; Xie, Guanti
Abstract: Deep learning methods, which have strong capabilities for mapping highly nonlinear relationships with acceptable calculation speed, have been increasingly applied for water quality prediction in recent studies. However, it is argued that the practicality of deep learning methods is limited due to the lack of physical mechanics to explain the prediction results of water quality changes. A knowledge gap exists in rationalizing the deep learning results for water quality predictions. To address this gap, an interpretable deep learning framework was established to predict the spatiotemporal variations of water quality parameters in a large spatial region. Mereological, land-use, and socioeconomic variables were adopted to predict the daily variations of stream water quality parameters across 138 sub-catchments in a total of over 575, 250 km 2 in southern China. The coefficients of determination of chemical oxygen demand (COD), total phosphorus (TP), and total nitrogen (TN) predictions were over 0.80, suggesting a satisfactory prediction performance. The model performance in terms of prediction accuracy could be improved by involving land-use and socioeconomic predictors in addition to hydrological variables. The SHapley Additive exPlanations method used in this study was demonstrated to be effective for interpreting the prediction results by identifying the significant variables and reasoning their influencing directions on the variation of each water quality parameter. The air temperature, proportion of forest area, grain production, population density, and proportion of urban area in each sub-catchment as well as the accumulated rainfall within the previous 3 days were identified as the most significant variables affecting the variations of dissolved oxygen, COD, ammoniacal nitrogen(NH3 –N), TN, TP, and turbidity in the stream water in the case area, respectively. Graphical abstract: Image 1 Highlights: An innovative interpretable deep learning method on water quality predictions. The SHapley Additive exPlanations method could interpret the prediction results. Economic categorical data could explain water quality variations at a large scale. The prediction accuracy could be improved by involving land-use predictors.